2011
DOI: 10.1186/1471-2202-12-123
|View full text |Cite
|
Sign up to set email alerts
|

Heightened inflammasome activation is linked to age-related cognitive impairment in Fischer 344 rats

Abstract: BackgroundMembers of the mammalian nucleotide binding domain, leucine-rich repeat (LRR)-containing receptor (NLR) family of proteins are key modulators of innate immunity regulating inflammation. Our previous work has shown that among the members of this family, NLRP1/NALP1, present in neurons, plays a crucial role in inflammasome formation and the production of the inflammatory cytokines interleukin (IL) -1β and IL-18 after various types of central nervous system injury.ResultsWe investigated whether age-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 49 publications
8
96
0
Order By: Relevance
“…In models of brain ischemia, evidence for inflammasome activation has been reported with elevations in inflammatory proteins such as ASC, and caspase-1. Our previously published studies demonstrated elevations in inflammasome proteins in the hippocampus of aged rats [41,42]. Consistent with our findings, others have demonstrated increased pro-inflammatory cytokine levels in middle-aged female rats [43].…”
Section: Discussionsupporting
confidence: 93%
“…In models of brain ischemia, evidence for inflammasome activation has been reported with elevations in inflammatory proteins such as ASC, and caspase-1. Our previously published studies demonstrated elevations in inflammasome proteins in the hippocampus of aged rats [41,42]. Consistent with our findings, others have demonstrated increased pro-inflammatory cytokine levels in middle-aged female rats [43].…”
Section: Discussionsupporting
confidence: 93%
“…For example, probenecid, an FDA-approved drug for the treatment of gout and hyperuricemia, inhibits inflammasome activation by high extracellular K þ in cultured neurons and astrocytes 18 and has been shown to decrease caspase-1 in the brain of aged rats. 76 Moreover, glyburide, typically used in the treatment of diabetes mellitus, inhibits NLRP3 inflammasome activation; 77 however, to date, glyburide has not been shown to inhibit inflammasome activation in the CNS. Other substances such as YVAD, PPADs, KN-62, and antibiotics ( Figure 3) have been suggested as possible therapeutics to block inflammasome activation, but these substances have not been successfully tested in the CNS.…”
Section: Inflammasome Activation After Brain and Spinal Cord Injurymentioning
confidence: 99%
“…[27][28][29][30][31] Neuronal Nlrp1 increased in rats submitted to spinal cord or sciatic nerve injury, 29,32 and in aging rat hippocampus or ethanol treated hippocampal slice cultures. 33,34 Aim2 induced pyroptosis in rat cortical neuron cultures and traumatic brain injury. 35 Nlrp1 has been reported in human brain pyramidal neurons 36 and inflammasome receptor mRNAs were observed in human neuron cultures and human Rasmussen's encephalitis.…”
mentioning
confidence: 97%